1975
DOI: 10.1021/jm00239a001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of some 10-substituted 2,3-dihydroimidazo[2,1-b]quinazolin-5(10H)-ones, a new class of bronchodilators

Abstract: On treatment of N-substituted isatoic anhydrides with 2-methylmercaptoimidazolines, 10-substituted imidazo[2,1-b]quinazolin-5(10H)-ones are obtained. Several members of this class exhibited pronounced broncholytic activity. The structure-activity relationships (based on results obtained in the guinea pig histamine aerosol test) of these nonsympathomimetic bronchodilators are discussed. In addition, the detailed pharmacological evaluation of two analogs found to be five to ten times more active than theophyline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…In combination with the 2-chloroethylamino grouping, they form novel 2-chloroethylphosphamides chemically related to cyclophosphamide, [10] one of the most common cancerostatics today. Although a number of N-substituted anthranilamides are already known, [11] we intended to synthesize a series of N-methylanthranilamides containing either a quincorine or quincoridine unit as a bulky, functionalized substituent.…”
Section: Results and Discussion A) N-methylanthranilamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with the 2-chloroethylamino grouping, they form novel 2-chloroethylphosphamides chemically related to cyclophosphamide, [10] one of the most common cancerostatics today. Although a number of N-substituted anthranilamides are already known, [11] we intended to synthesize a series of N-methylanthranilamides containing either a quincorine or quincoridine unit as a bulky, functionalized substituent.…”
Section: Results and Discussion A) N-methylanthranilamidesmentioning
confidence: 99%
“…[11] By reaction of 1 with the aminomethyl derivatives of QCD and QCI (2aϪc and 3aϪc), we synthesized the corresponding anthranilamides 4Ϫ9 (Scheme 2). Scheme 2 The course of the reaction was followed easily by monitoring the evolution of carbon dioxide.…”
Section: Results and Discussion A) N-methylanthranilamidesmentioning
confidence: 99%
“…and spectroscopic data (IR, 1 H and 13 C NMR) which are in good agreement with the reported values. These data are provided below in order of their entries in Table 1 as 7,64.1,55.3,28.9,26.8,23.7,19.9. N,.…”
Section: General Procedures For Condensation Of Amine and Carbon Disulmentioning
confidence: 99%
“…A literature survey revealed that imidazo [2,1-b]quinazolinones, imidazo [4,5-c]quinolin-4(5H)-one derivatives exhibited potent bronchodilatory activites [3,4]. Recent reports from these laboratories also indicate that fused heterocyclic quinazolinone ring systems exhibit potent bronchodilatory activity [5−7].…”
Section: Introductionmentioning
confidence: 99%